2009
DOI: 10.1111/j.1365-3040.2009.01952.x
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal suspensions of clay or titanium dioxide nanoparticles can inhibit leaf growth and transpiration via physical effects on root water transport

Abstract: A laboratory investigation was conducted to determine whether colloidal suspensions of inorganic nanoparticulate materials of natural or industrial origin in the external water supplied to the primary root of maize seedlings (Zea mays L.) could interfere with water transport and induce associated leaf responses. Water flow through excised roots was reduced, together with root hydraulic conductivity, within minutes of exposure to colloidal suspensions of naturally derived bentonite clay or industrially produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
202
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 482 publications
(216 citation statements)
references
References 39 publications
(78 reference statements)
8
202
2
4
Order By: Relevance
“…Another reason for the observed changes might be due to the inhibition of water and nutrient uptake as a result of CuO NPs exposure. A previous study by Asli and Neumann (2009) showed that titanium dioxide nanoparticles interfered with the ability of maize by forming aggregates along the root cell walls.…”
Section: Discussionmentioning
confidence: 98%
“…Another reason for the observed changes might be due to the inhibition of water and nutrient uptake as a result of CuO NPs exposure. A previous study by Asli and Neumann (2009) showed that titanium dioxide nanoparticles interfered with the ability of maize by forming aggregates along the root cell walls.…”
Section: Discussionmentioning
confidence: 98%
“…Toxicity tests using hydroponics to expose terrestrial plants do show some toxic effects [97]. In comparison, artificial or natural soils (OECD 208, terrestrial plant test) usually result in little or no phytotoxcity [98,99]. Commonly used endpoints such as germination and root growth have so far shown limited sensitivity to ENMs, even in hydroponic settings [100].…”
Section: Sensitive Endpoints For Soil Organismmentioning
confidence: 99%
“…Uptake of nanoparticles into plant leaves has been proposed to occur through small pores in the cuticle (< 5 nm) or through stomatal apertures (21). Cell wall pores are smaller than ten nanometers and the cell wall is expected to be a tight sieve which does not allow nanoparticles migration (34). Furthermore, it should be considered that translocation of nanoparticles from one leaf to another would require complex translocation mechanisms.…”
Section: Translocation Of Nanoparticlesmentioning
confidence: 99%